THE ANALYSIS OF CLASS OBSERVATION TO UNDERSTAND THE EXISTING MODEL OF TEACHING (The Journal of Educational Development, 2014)
This research focused on implementing class observation to get the whole idea of what existing models applied by the teachers to carry out their instructional activities were like. There were two state and two private elementary schools observed in this study. Observing class activities were accompanied with analyzing class teaching documents such as RPP and review paper to get the idea of what the existing model applied by the teachers was like. Yet, this study is focusing only on class observation. The research objective was to find out the quality of the existing model for teaching English in year 4 of the elementary school.  The method was carrying out class observations amounting from four to five times to each class.  The observer sat at the back of the class watching the activities and noted down what the teacher and students did along the period.  The note was later changed into field notes, giving comments after several minutes observation, focusing what the teacher did and what the students responded to what the teacher instructed them to do. The result showed that students responded accordingly to the teachers’ instruction either in group or individual work.  Thus, to get students’ involvement for the whole period, teachers have to be well prepared in terms of both materials and techniques. They can be written completely in their teaching preparation (RPP)